Tekanan Internal dan Eksternal, Etika Identitas Perusahaan, Islamic Social Responsibility dan Kinerja Keuangan : Studi pada Bank Syariah di Kawasan ASEAN - Fitri Laela Wijayati (EBBANK, 2017)
The purpose of this study is to indentified relationship between internal dan eksternal pressure as an atecedence to Corporate Ethical identity (CEI) disclosure dan Islamic Social Responsibility (ISR) disclosure with sharia’ bank performance. This study used two control variabel GPP per capita and branch sharia’ bank amount.  The sample of this study is sharia bank in ASEAN  which used panel data in periode 2013-2016 with total sample is 92 sample. Used Partial Least Square (PLS) analysis data to analysis model fit and analysis of each variable.  This study found that fianncial resources as an internal pressure proxied hasn’t relationship with CEI but has relationship with ISR. Management Discussion Analysis has relationship with CEI and ISR, concentration of shareholding as external pressure proxied hasn’t relationship with CEI and ISR. CEI and ISR has relationship with sharia bank performance